Corrigendum to ‘Alantolactone inhibits proliferation, metastasis and promotes apoptosis of human osteosarcoma cells by suppressing Wnt/β-catenin and MAPKs signaling pathways’ [Genes & Diseases 9 (2022) 466–478] - Yang, Chunmei; Zhang, Lulu; Huang, Huakun; Yuan, Xiaohui; Zhang, Ping; Ye, Caihong; Wei, Mengqi; Huang, Yanran; Luo, Xiaoji; Luo, Jinyong (Genes & diseases, 2023)
[This corrects the article DOI: 10.1016/j.gendis.2020.07.014.].